2022
DOI: 10.1371/journal.pone.0264612
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of maternal and newborn health service utilization across the continuum of care in Ethiopia: A multilevel analysis

Abstract: Background The continuum of care for maternal and newborn health is a systematic approach for delivery of an integrated effective package of life-saving interventions throughout pregnancy, childbirth, and postpartum as well as across levels of service delivery to women and newborns. Nonetheless, in low-income countries, coverage of these interventions across the life cycle continuum is low. This study examined the predictors of utilization of maternal and newborn health care services along the continuum of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 35 publications
(73 reference statements)
2
13
1
Order By: Relevance
“…At the median and highest quantiles, women from the poorest wealth quintiles had a lower COC compared to those from the richest. In line with our finding, a study indicated that the COC is low for women from the poorest households [28]. The low COC among the poorest women implies that the policies in place are not sufficient to compensate for the disadvantages associated with poverty.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…At the median and highest quantiles, women from the poorest wealth quintiles had a lower COC compared to those from the richest. In line with our finding, a study indicated that the COC is low for women from the poorest households [28]. The low COC among the poorest women implies that the policies in place are not sufficient to compensate for the disadvantages associated with poverty.…”
Section: Discussionsupporting
confidence: 88%
“…The COC is influenced by a range of factors such. as individual and community characteristics [17,[20][21][22][23], reproductive characteristics [18,[24][25][26][27][28] and socio-economic characteristics [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The low rate of the fourth ANC follow-up is usually common in studies undertaken in Ethiopia. Women may not be able to attend subsequent follow-ups because of distance, low level of education, and/or poor wealth index [ 38 40 ]. This was also documented in studies from other low-income countries [ 41 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…7 Other previous studies in Ethiopia used either of the indicators like; at least one ANC visit at least four ANC visits the timing of first ANC visits services received during ANC visits type of health-care provider visited, and quantity of contacts [16][17][18][19] with possible individual, and household (HH)-related determinants of use. [20][21][22][23] In this study, to provide a good summary of information all of the available mixes of indicators were exhaustively used. Additionally, it is the first study using the 2019th Ethiopian Mini Demographic, and Health Survey.…”
Section: Introductionmentioning
confidence: 99%